Physician-nurse attitudes toward collaboration in Istanbul's public hospitals - ERDİM, AYLİN (PERGAMON-ELSEVIER SCIENCE LTD, 2005)
The need for greater collaboration between nurses and physicians in clinical practice is essential to improve patient care and worker satisfaction. This study used t-tests and logistic regression to test four research hypotheses concerning attitudes toward physician-nurse collaboration in Istanbul, Turkey. The study found that nurses express more positive attitudes toward collaboration than physicians. Noteworthy was the finding that male physicians expressed more positive attitudes toward collaboration than female physicians. Residents and those employed in secondary institutions were also more likely to express more positive attitudes toward collaboration than permanent physicians and those employed in tertiary hospitals. (c) 2004 Elsevier Ltd. All rights reserved.
Keywords: collaboration; physician-nurse; attitudes; gender; UNITED-STATES; CRITICAL-CARE; COMMUNICATION; QUALITY; COST; PERCEPTIONS; DOCTORS; IMPACT; MODEL; WORK